Selling your produce - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2002)
That old saying the world is your market place is getting new meaning with the spread of the Internet. Even if you cannot join it yourself, there will be an organisation able to publicise you. Take to take a look on the World Wide Web at...